HARMONIZATION OF QRIS AND PADG REGULATIONS NO. 21/18/PADG/2019 IN INDONESIA'S DIGITAL PAYMENT SYSTEM - Wafiya; Edi Hermansyah (JOURNAL OF LAW AND NATION, 2026)
The transformation of the digital payment system in Indonesia presented new challenges in terms of regulation, particularly concerning the standards of the Quick Response Code Indonesian Standard (QRIS) and the legal status of the Regulation of the Members of the Board of Governors (PADG) No. 21/18/PADG/2019. This study aimed to identify regulatory dis harmonization within the digital payment legal system, analyze the position of PADG in the national legal structure, and explore efforts toward legal harmonization. A normative juridical approach and vertical-horizontal synchronization analysis were employed. The results of the study showed that regulations related to QRIS experienced overlapping authorities between Bank Indonesia and the Financial Services Authority (OJK), the absence of a specific law on digital payment systems, and a lack of policy integration among institutions. The role of PADG No. 21/18/PADG/2019 as a technical legal instrument from Bank Indonesia was implementation rather than normatively structural, and thus was not strong enough to provide broad legal certainty. Legal harmonization efforts were deemed crucial to be carried out systematically through three approaches: (1) restructuring regulations based on the principle of lex specialis derogat legi generali; (2) drafting a National Digital Payment System Law as a comprehensive legal umbrella; and (3) strengthening coordination among regulatory and supervisory institutions such as Bank Indonesia, OJK, and the Ministry of Finance. Such harmonization needed to be not only structural but also substantive and adaptive to the development of financial technology.